Design and fabrication of touch-sensitive polymeric optical fibre (POF) fabric. Issue 11 (2nd November 2019) - Tan, Jeanne; Bai, Ziqian; Ge, Lan; Shao, Li; Chen, Amy
Abstract: Polymeric optical fibres (POFs) can be integrated into a textile structure for illuminative fashion and interior fabric applications. In this study, the development of a touch-sensitive POF fabric system through the integration of conductive yarns and an electronic controlling system was explored. Distinct from conventional sensor applications, the capacitive sensor used in this study was embedded into the textile structure using conductive yarns via experimentations with different weave structures. With the embedded controlling system and RGB light-emitting diodes, the POF fabrics were able to transfer sensory signals into illumination. This study combined novel weaving techniques, different materials and electronic system development to develop a multi-touch interface based on textile capacitive sensors that can sense both touch contact and non-contact/proximity. The final prototype can be washed up to 10 laundry cycles. The results demonstrated that multiple functionalities can be integrated into the structure to produce an interactive textile based product.